The Increasing Prevalence of Diabetes Mellitus in COVID-19 Patients: Why? Life Sciences-Medicine - Khalid, Sufian; Ismail Osman Farah, Khadeja; AA, Awadalkareem; Kheir, Musa; M. Abdelrahim, Hisham; lmam Awadelkareim, Motwakil; Elsayed, Ahmed; Osman Elamin Bushara, Mohamed; A. Osman, Ahmed; M. Alshehri, Ali; Abdullah Natto, Hatim; H. Sinky, Tassnym; et al. (International Journal of Life Science and Pharma Research, 2022)
Coronavirus infection disease 2019 (COVID-19) is caused by SARS COV-2 and it has been increasing continuously in a number of cases and mortalities. COVID-19 had caused more than 197 million infections and 4 million deaths. This study aimed to assess the prevalence, risk factors and outcome of Diabetes Meletus (DM) among COVID-19 patients. Prospective, cross-sectional, hospital-based study conducted in which 400 COVID-19 patients enrolled in COVID-19 isolation centers in North Sudan. In this study, we noticed that most of the participants were males and constituted 275 (68.9%) of the study participants, the majority of participants’ ages ranged were between 40 to 60 years and was 150 (37.4%). The prevalence of DM was found to be 49.25% among the study participants. Diabetics were significantly more likely to have a respiratory rate higher than 30 (P=0.012), and oxygen saturation less than 93% (P<0.001), to develop shock (P=0.004), to require oxygen therapy (P<0.001), to be intubated (P<0.001), to develop respiratory failure and organ failure (P<0.001), and to have a poorer outcome (P<0.001). New-onset diabetes occurred in 20 (5%) participants and their mortality was higher compared to non-patients with diabetes (P=0.04). The total mortality of participants was 15.8%, factors associated with poorer outcomes were older age (P<0.001), and having type I diabetes (P=0.025). The prevalence of diabetes is very high among COVID-19 patients, and is associated with a more severe disease and a poorer outcome. New onset diabetes was associated with poorer outcomes compared to non-diabetics. More researches requested to discover more risk factors and complications associated with Covid- 19.